A Prudent dietary pattern is inversely associated with liver fat content among multi‐ethnic youth. Issue 6 (9th December 2020) - Perng, Wei; Harte, Robyn; Ringham, Brandy M.; Baylin, Ana; Bellatorre, Anna; Scherzinger, Ann; Goran, Michael I.; Dabelea, Dana
Summary: Objectives: To identify dietary patterns associated with hepatic fat fraction (HFF), a measure of liver fat content and risk factor for non‐alcoholic fatty liver disease, in a prospective study of 397 multi‐ethnic youth. Methods: We obtained information on habitual dietary intake via the Block Kids Food Frequency Questionnaire at age 6 to 15 years ('T1') and 12 to 19 years ('T2'), and measured HFF using magnetic resonance imaging at T2. We derived dietary patterns via principal components analysis and examined associations with ln‐transformed HFF using linear regression models that accounted for maternal education, gestational diabetes exposure and smoking habits; and child pubertal status, BMI and physical activity. Results: At T1, none of the dietary patterns identified were associated with HFF measured at T2. At T2, a Prudent dietary pattern characterized by high fruit and vegetable intake was inversely associated with HFF (−0.08 [95% CI: −0.16, −0.00]). Similarly, increased adherence to the Prudent pattern across T1 and T2 corresponded with lower ln‐HFF (−0.11 [−0.18, −0.04] units). On the other hand, adherence to a Western pattern comprising fried foods and refined carbohydrates at T2 correlated with higher HFF among non‐Hispanic White participants (0.16 [0.06, 0.26]). These findings persisted after accounting for child BMI. Conclusions: Even in healthy youth, a diet high in fruits and vegetables is associated with lower HFF, whereas a diet high in fried foods and refined carbohydrates is related to higher HFF. Dietary changes may serve as an early preventive measure to mitigate liver fat accrual.